Specimen dynamicum (1695) First part - von Leibniz, Gottfried Wilhelm; Másmela Arroyave, Carlos (Estudios de Filosofía, 1992)
Since we spoke for the first time about a new science of dynamics, which has yet to be founded, a number of prominent men have made known in different places their intentions for a more detailed exposition of this doctrine since our time is not yet enough For a book, we therefore want to present here a project that at least can already give some light, and that perhaps one day will be restored to us with interest and compound interest, when it is achieved by men who, by making use of both a force of thought and from a subtlety of style, move to the manifestation of your opinions. His judgment is always desired by us and, as is to be expected, useful for the realization of our work.